Tracking Subsurface Active Weathering Processes in Serpentinite. Issue 6 (16th March 2021) - Tominaga, Masako; Ortiz, Estefania; Einsle, Joshua Franz; Ryoichi Vento, Noah Francis; Schrenk, Matthew O; Buisman, Iris; Ezad, Isra S.; Cardace, Dawn
Abstract: We conducted a novel study to capture the on‐going advancement of mineral weathering within a serpentinite formation by using an integrated approach of multi‐scale quantitative rock magnetic analyses and nano‐resolution geochemical imaging analyses. We studied a suite of rock samples from the Coast Range Ophiolite Microbial Observatory (CROMO) in California to conduct rock magnetic analyses enabling us to determine character of Fe‐bearing minerals and to predict locations of reaction boundaries among various stages of weathering. QEMSCAN® and other electron micro‐imagery analyses highlighted microstructural changes in amorphous minerals, and possible changes in porosity and coincides with the iron‐enrichment region. This iron enrichment indicates initiation of iron (‐oxides) nucleation, resulting in extremely fine gain magnetite formation. This is a newly documented mode of magnetite production in serpentinites and enhances the application of magnetite abundance as a proxy for the degree and extent of water‐rock interaction in mantle peridotite and serpentinite. Plain Language Summary: Accounting for the range of weathering processes on Earth enables us to understand the intertwined processes related to climate change, connect regional and global ecosystems, and evaluate the planet's chemical budget. We used quantitative rock magnetic and micro‐scale analyses to capture the advancement of weathering in mineral phases, particularly in clay‐rich formations and soils in core samples extracted from subsurface rock formation of the Coast Range Ophiolite Microbial Observatory where the characteristics of the clay‐rich serpentinite impact microbial populations in deep biosphere. We capture weathering fronts based on information related to the physical condition of weathering phases within the boreholes and micro‐scale imagery of mineral phases. By focusing, on how iron‐rich regions are formed in the different mineral phases and the corresponding changes where water reacts with minerals, we identify where weathering is currently taking place at a micro‐scale, that is, the foremost front of this chemical phenomena and associating changes in physical conditions (porous spaces in the rocks) that could shed a new light on the habitability of deep biosphere. Key Points: A suite of rock magnetic analyses suggests a sequence of in situ weathering phases within serpentine formations in depths We identify a layer within CROMO serpentine formations where seasonal hydrogeology advances weathering processes We identify changes in porosity structure in mineral phases using micro‐scale imagery that suggests where weathering is currently taking place in serpentine